Characteristics of Tc-MEP Waveforms in Spine Surgery for Patients with Severe Obesity. Issue 24 (15th December 2021) - Kobayashi, Kazuyoshi; Ando, Kei; Yoshida, Go; Ando, Muneharu; Kawabata, Shigenori; Yamada, Kei; Kanchiku, Tsukasa; Fujiwara, Yasushi; Taniguchi, Shinichirou; Iwasaki, Hiroshi; Shigematsu, Hideki; Tadokoro, Nobuaki; et al.
Abstract : In transcranial motor evoked potential monitoring in spine surgery, the sensitivity and specificity of an amplitude decrease of ≥70% for prediction of neurologic complications were similar in severely obese patients (body mass index >35 kg/m 2 ) and all other patients. However, cases with undetectable waveforms were more common among severely obese patients. Abstract : Study Design: Prospective multicenter study. Objective: The aim of this study was to evaluate transcranial motor evoked potential (Tc-MEP) waveform monitoring in spinal surgery for patients with severe obesity. Summary of Background Data: Spine surgeries in obese patients are associated with increased morbidity and mortality. Intraoperative Tc-MEP monitoring can identify neurologic deterioration during surgery, but has not been examined for obese patients. Methods: The subjects were 3560 patients who underwent Tc-MEP monitoring during spine surgery at 16 centers. Tc-MEPs were recorded from multiple muscles via needle or disc electrodes. A decrease in Tc-MEP amplitude of ≥70% from baseline was used as an alarm during surgery. Preoperative muscle weakness with manual muscle test (MMT) grade ≤4 was defined as a motor deficit, and a reduction of one or more MMT grade postoperatively was defined as deterioration. Results: The 3560 patients (1698 males, 47.7%) had a mean age of 60.0 ± 20.3 years. Patients with body mass index >35 kg/m 2 (n = 60, 1.7%) were defined as severely obese. Compared with all other patients (controls), the rates of preoperative motor deficit (41.0% vs. 29.6%, P < 0.05) and undetectable baseline waveforms in all muscles were significantly higher in the severely obese group (20.0% vs. 1.7%, P < 0.01). Postoperative motor deterioration did not differ significantly between the groups. The sensitivity and specificity of the alarm criterion for prediction of postoperative neurologic complications were 75.0% and 83.9% in severely obese patients and 76.4% and 89.6% in controls, with no significant difference between the groups. Conclusion: Tc-MEPs can be used in spine surgery for severely obese cases to predict postoperative motor deficits, but the rate of undetectable waveforms is significantly higher in such cases. Use of a multichannel waveform approach or multiple modalities may facilitate safe completion of surgery. Waveforms should be carefully evaluated and an appropriate rescue procedure is required if the alarm criterion occurs. Level of Evidence: 3